Biofunctional Excipients: Their Emerging Role in Overcoming the Inherent Poor Biopharmaceutical Characteristics of Drugs - Milad Reda Qelliny; Wesam W. Mustafa; Adel Al Fatease; Ali H. Alamri; Raid Alany; Hamdy Abdelkader (Pharmaceutics)
Background/Objectives: With advancements in biomaterial sciences, biofunctional excipients have emerged to focus on solving issues with the drugs’ inherent biopharmaceutical characteristics such as poor solubility, permeability, in vivo dissolution, and effective targeting. These advanced excipients significantly impact drug solubility, dissolution rates, absorption rates, permeation rates, penetration ability, targeting ability, and pharmacokinetic profiles. Methods: A literature review of recently published articles was prepared. Data were collected using scientific search engines. This review provided a detailed discussion of various biofunctional excipients including smart polymers, targeted polymers, bioadhesive polymers, lipids, amino acids, cyclodextrins, and biosurfactants. Each category was discussed in detail concerning its biofunctional applications, the mechanisms underlying these biofunctions, and examples of their effects on drug performance. Results: The data obtained indicated that the rapid advances in the manufacturing of pharmaceutical excipients have resulted in the development of a diverse array of smart or intelligent excipients that play a crucial role in enhancing inherent poor biopharmaceutical characteristics. Conclusions: These advancements have also facilitated the development of various drug delivery systems, including immediate, controlled, sustained, and targeted drug release systems. Also, numerous nano-based delivery systems have emerged utilizing the newly produced excipients.